1986
DOI: 10.1159/000199333
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Retrograde Cholangiopancreatography in Sudanese Diabetics

Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) was performed in 40 Sudanese patients with diabetes mellitus. 25 were insulin-dependent and 15 were noninsulin-dependent. ERCP was normal in all the patients with insulin-dependent diabetes. Two patients with noninsulin-dependent diabetes had pancreatographic changes compatible with minimal-change pancreatitis. Diabetes mellitus in Sudan unlike in other tropical countries is not associated with structural changes in the exocrine pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…2). This is corroborated by the only ERP study in subjects with primary DM (25 type 1 and 15 type 2) 34 from Sudan, which showed normal pancreatogram in type 1 DM and minimal changes in 2 of 15 type 2 DM. Analysis of other ERP and magnetic resonance cholangiopancreatography (MRCP) studies in people with diabetes is confounded by the fact that they have included variable proportion of symptomatic patients with suspected pancreatobiliary disease 12,26 or did not provide any clinical history.…”
Section: Resultssupporting
confidence: 62%
“…2). This is corroborated by the only ERP study in subjects with primary DM (25 type 1 and 15 type 2) 34 from Sudan, which showed normal pancreatogram in type 1 DM and minimal changes in 2 of 15 type 2 DM. Analysis of other ERP and magnetic resonance cholangiopancreatography (MRCP) studies in people with diabetes is confounded by the fact that they have included variable proportion of symptomatic patients with suspected pancreatobiliary disease 12,26 or did not provide any clinical history.…”
Section: Resultssupporting
confidence: 62%
“…However, ERCP may cause several potential complications including bleeding, cholangitis, perforation, and post-ERCP pancreatitis [3][4][5] The reported data on ERCP utility, outcomes, and safety from well-developed and less developed countries have been widely different. Only few ERCP descriptive studies were reported from Arab countries [6][7][8][9][10], and to the best of our knowledge there are no such available data published from Libya. The aim of the present study was to review the indications, findings, technical success, and outcomes of diagnostic and therapeutic ERCP procedures in a large cohort of patients admitted to a single tertiary centre in Libya.…”
Section: Introductionmentioning
confidence: 99%